MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN SOSIOLOGI DI KELAS X MAS.TI BATANG KABUNG PADANG - Candra, Flaxseng; Rianto, Slamet; Marleni, Marleni (Pendidikan Sosiologi, 2013)
This research beginning from several problems. That the writer observed at MAS.TI Batang Kabung Padang namely the headmaster that has given lack motivation toward his students. The teacher who taught sociology was taught by other teacher that was not his major. The time schedule for sociology was vary limited, only two hours in a week, one class meeting is only thirty minutes this research meant to analize study motivation of students in learning sociology. For the ten the class at MAS.TI Batang Kabung Padang.The kinds of this research was inclusive as descriptive research. The population and sampel in this research was for all srudents class in MAS.TI Batang Kabung Padang that was listed in academic year 2013/2014 that was aprrotimately us students. The instrument that was used in this research was angket motivation.The results of this research indicated that the student motivation as MAS.TI Batang Kabung Padang to study sociology was enough evaluated. This can be viewed from percentage results positive angket MAS.TI Batang Kabung Padang of student motivation was 60 % and the results of negative angket of student motivation was 62,9 %.Â The teacher motivation at MAS.TI Batang Kabung Padang in implementing this sociology activities was inclusive strong. This can be viewed from the results of positive angket of the headmaster study activities motivation was 69,4 %. The motivation of headmaster policy at MAS.TI Batang Kabung Padang in managing his school was enough evaluated in managing madrasah. This can be viewed from the results of percentage positive angket on the headmaster policy motivation was 58,5 % and the results of 65,4%.